2019
DOI: 10.1002/app.48234
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticles improved biocompatibility and removal of middle molecule uremic toxin of polysulfone hollow fiber membranes

Abstract: Middle molecule uremic toxins constitute to a quarter of uremic toxins present in human blood. In a condition where these uremic toxins accumulate in bloodstream due to renal failure, blood purification process using a high performance membrane is required. Here, we develop biocompatible mixed matrix membranes (MMMs) made up of polysulfone (PSf) and iron oxide nanoparticles (Fe2O3 NPs) with the focus to remove middle molecule uremic toxin effectively. The MMMs were evaluated in terms of their biocompatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Membrane processes are classified based on their operational driving forces, which further depend on their separation mechanisms, such as sieving [ 38 ], solution-diffusion [ 39 ], adsorption [ 40 ], and electrochemical effects [ 41 ]. Thus, the driving forces include the gradients of pressure [ 42 , 43 , 44 , 45 ], potential [ 46 , 47 , 48 ], and concentration [ 49 , 50 ] across the membrane. Pressure driven membrane processes include MF [ 51 ], UF [ 52 ], NF [ 53 ], and RO [ 54 ].…”
Section: Membrane Processes Based On Various Separation Driving Forcesmentioning
confidence: 99%
“…Membrane processes are classified based on their operational driving forces, which further depend on their separation mechanisms, such as sieving [ 38 ], solution-diffusion [ 39 ], adsorption [ 40 ], and electrochemical effects [ 41 ]. Thus, the driving forces include the gradients of pressure [ 42 , 43 , 44 , 45 ], potential [ 46 , 47 , 48 ], and concentration [ 49 , 50 ] across the membrane. Pressure driven membrane processes include MF [ 51 ], UF [ 52 ], NF [ 53 ], and RO [ 54 ].…”
Section: Membrane Processes Based On Various Separation Driving Forcesmentioning
confidence: 99%
“…Said et al [ 112 ] reported the obtaining of polysulfone membrane functionalized with iron oxide for better biocompatibility and being able to remove the middle molecule uremic toxin effectively. It was shown that even though a high concentration of iron oxide was added, it displayed a reduction of protein adsorption and platelet adhesion while maintaining normal blood coagulation time and admissible complement activation [ 112 ]. Unfortunately, iron oxide nanoparticles have a tendency to form aggregates.…”
Section: Polysulfone Functionalized Membranes For Hemodialysismentioning
confidence: 99%
“…Iron oxide nanoparticle (Fe 2 O 3 NP) is another alternative additive. Said et al developed membranes made up of polysulfone and Fe 2 O 3 NPs, and found that these membranes have improved biocompatibility and excellent clearance of urea and lysozyme [ 122 ].…”
Section: The Toxicity Of Biomaterials For Blood Purificationmentioning
confidence: 99%